2003
DOI: 10.1029/2001jb000898
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of retreating slabs: 1. Insights from two‐dimensional numerical experiments

Abstract: [1] We use two-dimensional numerical experiments to investigate the long-term dynamics of an oceanic slab. Two problems are addressed: one concerning the influence of rheology on slab dynamics, notably the role of elasticity, and the second dealing with the feedback of slab-mantle interaction to be resolved in part 2. The strategy of our approach is to formulate the simplest setup that allows us to separate the effects of slab rheology (part 1) from the effects of mantle flux (part 2). Therefore, in this paper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
97
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 81 publications
(106 citation statements)
references
References 62 publications
(114 reference statements)
7
97
0
Order By: Relevance
“…Laboratory and numerical models [5,10,12,15,16,18,19,29,31] have shown that the process is mainly controlled by the interaction of the lithosphere with the surface and is one-sided, characterized by an unsubducted plate overlapping the subducting plate. Seismic tomography and Benioff Zone studies have shown that they penetrate down into the mantle assuming complex shapes [6,11,17,38,39].…”
Section: Modeling Subduction With Accelerated-bem Settingmentioning
confidence: 99%
“…Laboratory and numerical models [5,10,12,15,16,18,19,29,31] have shown that the process is mainly controlled by the interaction of the lithosphere with the surface and is one-sided, characterized by an unsubducted plate overlapping the subducting plate. Seismic tomography and Benioff Zone studies have shown that they penetrate down into the mantle assuming complex shapes [6,11,17,38,39].…”
Section: Modeling Subduction With Accelerated-bem Settingmentioning
confidence: 99%
“…Carlson and Melia, 1984;Jarrard, 1986;Garfunkel et al, 1986;Heuret and Lallemand, 2005). Laboratory (Funiciello et al, 2003a;Bellahsen et al, 2005) and numerical (Funiciello et al, 2003b;Stegman et al, 2006;Di Giuseppe et al, 2008;Di Giuseppe et al, 2009;Capitanio et al, 2010b) models of oceanic subduction showed that trench migration is controlled by geometrical (thickness and width of the plate) and rheological (density contrast, viscosity ratio) parameters of the subducting lithosphere. In the continental subduction scenario, Royden (1993) proposed the same two end-member classes: the advancing style (e.g.…”
Section: Magni Et Al: Numerical Models Of Slab Migrationmentioning
confidence: 99%
“…This property is critical in subduction as it prevents the unsubducted plate from sinking straight down [11].…”
Section: Modeling Subduction With Fmm-bemmentioning
confidence: 99%